2019
DOI: 10.1039/c9ay00759h
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of volatile organic compounds from patients and cell lines for the validation of lung cancer biomarkers by proton-transfer-reaction mass spectrometry

Abstract: Exhaled breath samples from 60 volunteers (30 lung cancer patients, 30 healthy people), and headspace VOCs from lung cancer cells (A549 and H1703) were analyzed using proton-transfer-reaction mass spectrometry (PTR-MS).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 46 publications
0
19
1
Order By: Relevance
“…A total of 139 studies were included in the present review. From the total of 60 cross-sectional clinical studies selected [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 ], 33 ...…”
Section: Statistics Of Included Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…A total of 139 studies were included in the present review. From the total of 60 cross-sectional clinical studies selected [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 ], 33 ...…”
Section: Statistics Of Included Studiesmentioning
confidence: 99%
“…From the total number of participants, 421 were children with 229 children having asthma and 192 children acting as the controls. Of the selected clinical studies, thirty-two of them reported that they used mixed expired breath [ 13 , 17 , 19 , 21 , 33 , 34 , 36 , 38 , 41 , 42 , 43 , 45 , 46 , 54 , 59 , 60 , 61 , 62 , 64 , 66 , 67 , 68 , 69 , 71 , 72 , 73 , 75 , 76 , 78 , 80 , 83 , 85 ] (consisting normally in a mixture of gaseous breath, that also includes the volatile components) collected by simple expiration in bags, tubes with absorbent materials or directly into the used instrumentation (as in the case of E-noses, for example). A total of twenty-two of them reported the use of alveolar breath [ 14 , 15 , 16 , 18 , 22 , 32 , 35 , 37 , 44 , 48 , 56 , 57 , 58 , 65 , 70 , 74 , 77 , 79 , 81 , 82 , 84 , …”
Section: Statistics Of Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations